Experimental Study on Drying Characteristics of Pomegranate Peels - Doymaz, Ibrahim (KOREAN SOCIETY FOOD SCIENCE & TECHNOLOGY-KOSFOST, 2011)
Drying kinetics of pomegranate peels has been experimentally investigated in a cabinet dryer. Drying experiments were performed at constant air velocity of 2.0 m/s and initial thickness of 2.8 cm for pomegranate peels, and 3 drying air temperatures of 50, 60, and 70 degrees C. The drying time decreased with increase in drying air temperature. Experimental data were fitted to 10 mathematical models. The fit quality of models on experimental data were evaluated using 3 statistical tests, coefficient of determination, reduced chi-square, and root mean square error. The statistical analysis concluded that the best model in terms of fitting performance was the Midilli et al. model. The effective diffusivity varied from 4.02 to 5.31x10(-9) m(2)/s over temperature range. Temperature dependence of the diffusivity was well documented by Arrhenius-type relationship. The activation energy was found to be 12.72 kJ/mol for pomegranate peels.
Keywords: activation energy; drying; diffusivity; modeling; pomegranate peel; THIN-LAYER; MOISTURE DIFFUSIVITY; ANTIOXIDANT ACTIVITY; APPLE POMACE; KINETICS; SLICES; L.; Food Science & Technology